Numerical methods for hyperbolic equations : theory and applications : an international conference to honour Professor E.F. Toro : proceedings of the International Conference on Numerical Methods for Hyperbolic Equations : Theory and Applications, Santiago de Compostela, Spain, 4-9 July 2011 /: theory and applications : an international conference to honour Professor E.F. Toro : proceedings of the International Conference on Numerical Methods for Hyperbolic Equations : Theory and Applications, Santiago de Compostela, Spain, 4-9 July 2011. (2013) - Unknown
No abstract available